Potensi Intoleransi Keagamaan Siswa Sekolah Di Jawa Dan Sulawesi - Imam Tholkhah (Badan Litbang dan Diklat Kementerian Agama RI, 2013)
This particular writing describes research upon the interest of students towards religious education and a developing potency for intolerance in public and religious schools. The research indicates that the students show a rather high interest towards religious teaching in schools. Teachers still can make religious teachings attractive. On the other hand, a minor amount of students still appear to be less interested in religious teachings. The minority stated that this is because of the monotonic and unattractive ways in which the teacher in conveys the information. Fortunately, the majority of the students continue to apply a high level of tolerance to religious teachings. This fact shows that religious teachers are still capable of teaching religious education that is relevant to the national education standards. However, there still remain students who lack tolerance towards religious teaching. There are indications that they provide support towards groups who apply discrimination, lack of respect, and intolerance to other groups with different practices or religion. Even though the level of intolerant students is low, the fact that it could expand remains possible, so precaution is still needed. If this particular potential for expansion is taken lightly, it may become a threat towards the nation because it has a potential to be a source of religious conflict. The development of multicultural understanding and tolerance in public or religious schools is one way to resolve this problem. Tulisan ini merupakan temuan penelitian yang menggambarkan minat siswa terhadap pendidikan agama dan potensi intoleransi keagamaan siswa yang berkembang di sekolah dan madrasah. Temuan itu menunjukkan bahwa minat siswa terhadap pendidikan agama sangat tinggi. Dan para gurupun masih menyampaikan pendidikan agama dengan menarik. Sebagian kecil siswa kurang berminat mempelajari agama. Mereka mengatakan metode mengajar guru agama tidak menarik atau membosankan. Mayoritas siswa di sekolah memiliki pandangan keagamaan yang toleran. Fakta ini menunjukkan bahwa guru agama mampu mengajarkan pendidikan agama sesuai dengan standar nasional pendidikan. Hanya saja terdapat sebagian siswa yang memiliki potensi intoleransi keagamaan. Di antara indikasinya adalah mereka memberikan dukungan pada kelompokkelompok yang berprilaku diskriminatif, tidak memberikan penghargaan, tidak menghendaki eksistensi pihak lain yang memiliki paham atau aliran keagamaan berbeda. Meskipun jumlah siswa yang intoleran minoritas di sekolah, pertumbuhan potensi intoleransi ini perlu dicegah, agar tidak berkembang luas. Kalau potensi ini dibiarkan berkembang, maka lama kelamaan dapat menjadi sumber konflik keagamaan yang dapat mengancam persatuan dan kesatuan bangsa. Di antara cara mencegahnya adalah melalui pengembangan wawasan multikultural dan pengembangan budaya toleransi di sekolah dan madrasah.